Morpho-phylogenetic evidence reveals Pseudolomaantha thailandica gen. et sp. nov. and Submultiguttulispora multiseptata gen. et sp. nov. in Chaetosphaeriaceae - Jing-Yi Zhang; Kevin D. Hyde; Jian Ma; Na Wu; Fatimah Al-Otibi; Li-Juan Zhang; Yong-Zhong Lu (MycoKeys)
Anamorphic chaetosphaeriaceous fungi exhibit high morphological variability and are distributed worldwide across terrestrial and aquatic habitats. During an ongoing taxonomic study of microfungi, two intriguing chaetosphaeriaceous hyphomycetes were collected from dead wood and dead bamboo stems in China and Thailand. A polyphasic approach, combining morphological characteristics and phylogenetic analysis of LSU and ITS sequence data, revealed that these fungi represent two new genera within Chaetosphaeriaceae. Pseudolomaantha and Submultiguttulispora are proposed for these new genera, and they exhibit non-phialidic and phialidic asexual morphs, respectively. Pseudolomaantha thailandica gen. et sp. nov. is characterized by a sporidesmium-like asexual morph with macronematous, mononematous conidiophores; monoblastic conidiogenous cells, and pyriform to obclavate, rostrate conidia bearing an apical appendage. Submultiguttulispora multiseptata gen. et sp. nov. is distinguished by macronematous, mononematous conidiophores, mono- to polyphialidic conidiogenous cells, and fusiform or ellipsoidal-fusiform, pale brown to olive green to brown conidia with filiform, hyaline appendages at both ends. Detailed descriptions, illustrations, and notes on the new collections are provided, along with a key to non-phialidic hyphomycetous genera in Chaetosphaeriaceae.